2008
DOI: 10.1891/1521-0987.9.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Community-Based Programs Serving U.S. Families With Huntington’s Disease: Perceived Barriers and Facilitators in the Residential Placement Process

Abstract: This article describes the contours of the residential care placement experience for social service staff health care providers, and their client families of patients with Huntington's disease. The purpose of this study was to determine the factors, conditions, and barriers encountered by outpatient clinical staff and families in the transition to skilled nursing care. A Long-Term Care Contact Survey was developed to (a) gather information about long-term care referral sites; (b) determine the factors consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…These centres provide regional care, but their services may not be accessible to all people with HD and their families. Healthcare services for people with HD also reflect local community resources, and a recent survey of HD programmes showed that there are few large cohorts of people with HD in residential care (Lechich et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These centres provide regional care, but their services may not be accessible to all people with HD and their families. Healthcare services for people with HD also reflect local community resources, and a recent survey of HD programmes showed that there are few large cohorts of people with HD in residential care (Lechich et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, while nurses perceived a need for strengthening and diversifying care options for HD patients, they also stressed the importance of providing quality care to these patients, and consequently, the need for ongoing education and training programs about HD. This view also complemented that expressed by other health professionals (Lechich et al ., ), as well as by the patients (Aoun et al ., ) and their carers (Baker, ), who identified a need for quality care delivered by suitably‐qualified staff. Additionally, there is a need for sufficient staff levels to enable these professionals to attend effectively to the needs of these individuals.…”
Section: Discussionmentioning
confidence: 94%
“…The nurses identified a need for alternative services in the community which could provide for adequate social and healthcare support. Such services could include the provision of proactive support (McGarva, ) from a multidisciplinary team of professionals (Williams et al ., ), the availability of domestic help and assistance with meals (Aoun et al ., ; McCabe et al ., ), and the provision of home technologies, for example, computerized communication devices (Lechich et al ., ). An alternative care option, which was also mentioned by study participants, was specialized residential homes.…”
Section: Discussionmentioning
confidence: 97%
“…Supportive care 17 is required from the initial discovery of HD in the family, throughout a lengthy disease trajectory that inevitably ends with institutionalization. 31 In NL, there are simply too few services and supports to meet the needs of affected individuals and their families. Those services that are available tend to be located in the capital city, many hours away for some study participants.…”
Section: Discussionmentioning
confidence: 99%
“…While nursing homes are the primary setting for patients in the middle and late stages of HD, the illness is difficult to manage, even with skilled professionals. 31 Accessing other skilled specialists was also perceived as difficult:…”
Section: Ignorance About Huntington Disease In Primary Carementioning
confidence: 99%